2010
DOI: 10.1159/000314232
|View full text |Cite
|
Sign up to set email alerts
|

Combined Papillated Bowen Disease and Clear Cell Atypical Fibroxanthoma

Abstract: We describe a case of papillated Bowen disease (PBD), associated with a clear cell atypical fibroxanthoma (CCAFXA). The epidermal lesion showed a bowenoid papillomatous growth pattern with histologic features suggestive of infection by human papilloma virus (HPV). In the dermis a neoplasm made up by spindled or polygonal cells with wide clear cytoplasm and moderate nuclear pleomorphism was found. Immunohistochemical characteristics of these two lesions were clearly different. The atypical cells of the intraepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 19 publications
1
11
1
Order By: Relevance
“…Recently, CD99, CD10 and c-kit (CD117) were described as sensitive antibodies of classic AFX. However, these antibodies have not been studied in most of the published CCAFX [2]. In our case showed positive staining with CD10.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Recently, CD99, CD10 and c-kit (CD117) were described as sensitive antibodies of classic AFX. However, these antibodies have not been studied in most of the published CCAFX [2]. In our case showed positive staining with CD10.…”
Section: Discussionmentioning
confidence: 56%
“…The tumour cells were positively stained with vimentin, CD68, CD10 and CD99. Tumour cells were negatively stained with S-100 protein, pan-CK, EMA, SMA and MART-1 [1][2][3][4][5]. SmithZagone et al, [6] recently reported focal HMB-45 and MART-1 expression in the giant cells of AFX.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical feature of our case differs from that of papillated Bowen's disease in that the surface was not verrucous or hyperkeratotic, moreover, there was no papillomatosis on a histopathological examination12. Unusual cases of melanocytic nevi having a similar clinical appearance have been reported as “lobulated melanocytic nevi”56.…”
Section: Discussionmentioning
confidence: 62%